Inovasi Pemanfaatan Limbah Kulit Kopi Menjadi Produk Yang Bernilai Tinggi Sebagai Pengembangan Produk Pada Gapoktan Desa Mulyorejo - Oktavinda, Diana; Dwi Natasya, Amelia; Syaifuddin, Ageng; Daffa Duta Perdana, Mohammad; Narisa, Defani; Angga Pranadaning, Fadila; Zahro Alifia Rohma, Sofiatus; Edwar Yudhistira, Gedion; Aini, Arifatul; Nurfaizeh, Nurfaizeh; laili, Nufilatul; Shofyan, Firdaus; Hermawan, Muhammad; Afreyna Fauziah, Difari (Institut Teknologi dan Sains Mandala, 2023)
Coffee is one of the plantation commodities that has quite high economic value among other plantation crops such as cocoa and tea. One of the villages as a smallholder coffee producer is the village of Mulyorejo. Mulyorejo Village is the largest coffee producing village out of nine villages in Silo District, Jember Regency. So far, coffee pod waste has caused many problems in its handling and is left to rot, stacked and burned, all of which have a negative impact on the environment, so we need to think about countermeasures. Coffee skin waste has the potential to be processed back into a product because it has a fairly high economic value. The activities carried out were in the form of counseling and demonstrations on the manufacture and introduction of Coffee Skin Tea products. The purpose of holding counseling activities is to increase target knowledge about the potential of coffee skin waste, the processing system of coffee skin waste, the benefits of coffee skin waste for health, and the nutritional content of coffee skin waste.